Foraging behaviour of cattle grazing semi-arid rangelands in the Sahel of Mali - Diarra, L.; Hiernaux, Pierre H.Y.; Leeuw, P.N. de (International Livestock Centre for Africa, 1995)
This paper deals with foraging behaviour of cattle grazing semi-arid rangelands in the Sahel of Mali. It discusses the location of study site, vegetation in the grazing orbit, herd management and livestock behaviour. Results on seasonal variation in feed supply, selection of the annual grazing orbit in accessible land and of the daily route in the grazing orbit, selection of herbage mass patches within landscape units and selection of species are also presented in the paper. Discussion on forage selection, selection of landscape units and of plant species, impact of cattle foraging vegetaion and rangelands N and P harvesting by livestock are the last topics examined in the paper.